P70Circulating microRNAs and outcome in patients with acute heart failure. (15th July 2014) - Goretti, E; Seronde, MF; Vausort, M; Gayat, E; Thum, T; Cohen-Solal, A; Wagner, DR; Mebazaa, A; Devaux, Y
Abstract: Purpose: Circulating microRNAs (miRNAs) have been extensively studied for their potential biomarker value in patients with acute coronary syndromes. However, the association between miRNAs and the diagnostic and prognostic in patients with acute heart failure (AHF) has received less attention. Methods: 294 patients with acute dyspnea (236 AHF and 58 non-AHF), and 44 patients with stable chronic heart failure (CHF), were included in this prospective, single-center case-control study. This study was set up in the emergency department and in the 10-bed cardiac intensive care unit of an academic hospital. Circulating levels of miR-1/-21/-23/-126/-423-5p were assessed by quantitative PCR in plasma samples obtained at admission and after 5 days. Results: At admission, levels of miR-21 and miR-23 were comparable among AHF, non-AHF and CHF patients. Levels of miR-1 were lower in AHF and stable CHF patients compared to non-AHF patients (p=0.0016). Levels of miR-126 and miR-423-5p were lower in AHF and in non-AHF patients compared to stable CHF patients (both p<0.001). All miRNAs had a poor diagnostic value for AHF. During the 5 days post admission, miRNA levels were stable in AHF patients. In non-AHF patients, levels of miR-23, miR-126 and miR-423-5p decreased over the same period. Interestingly, admission levels of miR-423-5p were lower in patients who were re-admitted to the hospital, mostly for cardiovascular disease, in the year following the index hospitalization compared to patients who were not (p=0.0001). Adjusted odds ratios [95% confidence interval] for one-year readmission was 0.70 [0.53-0.93] for miR-423-5p (p=0.01). Admission levels of the five miRNAs were not associated with one-year mortality. Conclusion: In AHF patients, low circulating levels of miR-423-5p at presentation are associated with hospital readmission. This study supports the value of miR-423-5p as prognostic biomarker of AHF.